(untitled) (REMUNOM, 2024)
Irrigation solutions develop a crucial role in endodontic treatment allowing the cleaning, disinfection and shaping of the root canal, once mere mechanical instrumentation is insufficient to effectively achieve these objectives. Among the irrigation options, Sodium Hypochlorite (NaOCl) stands out as the most efficient due to its remarkable properties, such as the ability to dissolve tissues and its low surface tension. However, it is essential to recognize that contact of NaOCl with tissues outside the root canal can provoke cytotoxic reactions, especially in cases of accidents during the procedure. This study aims to understand the relevance of sodium hypochlorite in endodontic therapy, identify accidents associated with this solution during irrigation and investigate their causes, treatments and preventive measures. In order to it, a literature review was conducted across various databases covering the period from 2014 to 2024. The results shows that accidents with NaOCl are rare and often result from professional errors. Extravasation of hypochlorite into periapical tissues is the most commonly reported accident, presenting symptoms such as intense pain, bleeding, and edema. The treatment aims to alleviate inflammatory symptoms and prevent infections by monitoring the accident it’s adequately solved. Although more severe occurrences are rare, the possibility of hospital referral should be considered if necessary. Preventive measures are fundamental to ensure the effectiveness of irrigation with NaOCl and to avoid adverse reactions in tissues external to the root canals. In summary, this study emphasizes the importance of professionals’ knowledge regarding the signs of accidents with sodium hypochlorite for effective diagnosis and treatment.